2022
DOI: 10.1016/s1473-3099(21)00751-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of two neutralising monoclonal antibody therapies, sotrovimab and BRII-196 plus BRII-198, for adults hospitalised with COVID-19 (TICO): a randomised controlled trial

Abstract: Background We aimed to assess the efficacy and safety of two neutralising monoclonal antibody therapies (sotrovimab [Vir Biotechnology and GlaxoSmithKline] and BRII-196 plus BRII-198 [Brii Biosciences]) for adults admitted to hospital for COVID-19 (hereafter referred to as hospitalised) with COVID-19. Methods In this multinational, double-blind, randomised, placebo-controlled, clinical trial (Therapeutics for Inpatients with COVID-19 [TICO]), adults (aged ≥18 years) hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
96
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(103 citation statements)
references
References 23 publications
3
96
1
3
Order By: Relevance
“…This decision is based on data from a positive study in which 1% of outpatients with symptomatic COVID-19 in the sotrovimab group versus 7% in the placebo group required hospitalization (relative risk reduction 85%, 97.24% CI 44–96%; P = 0.002) 206 despite the fact that no significant improvement in clinical outcomes was observed among adults treated while hospitalized with COVID-19 (ref. 207 ). Sotrovimab has in vitro activity against a broad range of VOCs including Omicron; therefore, this agent might be of clinical value in prophylaxis (pre-exposure and post-exposure) and as an early intervention in patients with cancer 116 , 203 , 208 , 209 .…”
Section: Alternatives To Vaccinationmentioning
confidence: 99%
“…This decision is based on data from a positive study in which 1% of outpatients with symptomatic COVID-19 in the sotrovimab group versus 7% in the placebo group required hospitalization (relative risk reduction 85%, 97.24% CI 44–96%; P = 0.002) 206 despite the fact that no significant improvement in clinical outcomes was observed among adults treated while hospitalized with COVID-19 (ref. 207 ). Sotrovimab has in vitro activity against a broad range of VOCs including Omicron; therefore, this agent might be of clinical value in prophylaxis (pre-exposure and post-exposure) and as an early intervention in patients with cancer 116 , 203 , 208 , 209 .…”
Section: Alternatives To Vaccinationmentioning
confidence: 99%
“…Interim futility analyses of two neutralizing monoclonal antibody therapies, namely sotrovimab and BRII-196 plus BRII-198, in a multinational, double-blind, randomized placebo-controlled phase III ACTIV-3 trial (NCT04501978) in hospitalized adults with COVID-19 have been reported [ 40 ]. There was no significant (based on 95% CI) difference between sotrovimab ( n = 182) and placebo ( n = 178) recipients with respect to a more favourable category on the pulmonary scale at day 5 (adjusted odds ratio 1.07; 95% CI 0.74–1.56), a more favourable category on the pulmonary-plus complication scale at day 5 (1.08; 0.74–1.58) and a more favorable sustained clinical recovery by day 90 (adjusted rate ratio 1.12; 0.91–1.37).…”
Section: Scientific Summarymentioning
confidence: 99%
“…There was no significant (based on 95% CI) difference between sotrovimab ( n = 182) and placebo ( n = 178) recipients with respect to a more favourable category on the pulmonary scale at day 5 (adjusted odds ratio 1.07; 95% CI 0.74–1.56), a more favourable category on the pulmonary-plus complication scale at day 5 (1.08; 0.74–1.58) and a more favorable sustained clinical recovery by day 90 (adjusted rate ratio 1.12; 0.91–1.37). Enrolment in the sotrovimab arm was halted on the basis of the analysis [ 40 ].…”
Section: Scientific Summarymentioning
confidence: 99%
“…The ACTIV-3 Therapeutics for Inpatients with COVID-19 (TICO) platform was developed to assess multiple candidate mAbs in individuals hospitalised with moderate or severe COVID-19 within 12 days of symptom onset. In The Lancet Infectious Diseases , the ACTIV-3 TICO Study Group 6 report the results of two neutralising mAb treatments (sotrovimab and BRII-196 plus BRII-198) that were provided in addition to standard of care, typically including remdesivir and corticosteroids, in a double-blind, randomised fashion, predominantly before the availability of SARS-CoV-2 vaccines, and were compared with a pooled placebo group. Enrolment into the trial was stopped early after a prespecified interim futility analysis in 536 participants in the modified intention-to-treat population found no improvement in odds of favourable pulmonary outcome scores on day 5 after infusion with either sotrovimab or BRII-196 plus BRII-198 compared with placebo.…”
mentioning
confidence: 99%
“…Based on intriguing results from the RECOVERY study on efficacy of casirivimab–imdevimab (REGN-COV2) in patients hospitalised with COVID-19, which showed benefit only in people who were retroactively determined to be seronegative for anti-spike IgG at randomisation, 7 similar serostatus-dependent effects could have been seen with sotrovimab or BRII-196 plus BRII-198, despite no overall benefit. In the study by the ACTIV-3/TICO Study Group, 6 513 of 536 patients in the mITT population had baseline anti-spike antibody levels measured, enabling a subgroup analysis stratified by serostatus. At the time of randomisation, 212 (41%) participants were positive for anti-spike neutralising antibodies.…”
mentioning
confidence: 99%